2016
DOI: 10.23887/jppundiksha.v49i3.9014
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Penggunaan Metode Eksperimen Dengan Pendekatan Inkuiri Dan Verifikasi Terhadap Hasil Belajar Siswa

Abstract: Differences in the Use of The Experimental Method of Inquiry and Verification ApproachTowards the Students Learning Results. This study was aimed to determine whether there is a difference in the understanding and the concept application as well as the scientific performance between the students who were given a lesson by using the experimental method with guided inquiry and verivication as well as informative approach (lecture). The type of this study is a true experimental study using the randomized pretestp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The findings of previous research also revealed that experimental-based science learning would have a significant learning impact because students could understand concepts independently (Rismaningsih, 2016;Subekti & Ariswan, 2016). Other research findings also reveal that the VAK model is appropriate in science learning because it maximizes three modalities (Nurmayani et al, 2017;Rahmadani et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The findings of previous research also revealed that experimental-based science learning would have a significant learning impact because students could understand concepts independently (Rismaningsih, 2016;Subekti & Ariswan, 2016). Other research findings also reveal that the VAK model is appropriate in science learning because it maximizes three modalities (Nurmayani et al, 2017;Rahmadani et al, 2021).…”
Section: Introductionmentioning
confidence: 84%
“…Learning activities will be more meaningful if students discover the concepts they learn scientifically for themselves. This experiment is one of the learning methods implementing experiments, so students will become more interactive and discover learning concepts (Restyani, 2018;Rismaningsih, 2016). Moreover, students also do not understand abstract things, so by finding their understanding, it will be easier for children to understand learning (Devi & Bayu, 2020;Diyantari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The normality test was carried out with the Saphiro-Wilk test on student pretest and posttest data. States that data is referred to as normal data if the significance is> 0.05 in the Saphiro-Wilk normality test [11]. States that if the data does not meet the normal distribution value, then parametric statistics cannot be used and need to use non-parametric statistical tests [12].…”
Section: Data Normality Testmentioning
confidence: 99%
“…One solution to increase student learning motivation is to use appropriate learning methods or media. Using appropriate teaching methods is one way to build interaction between teachers and students (Khaulani et al, 2019;Rismaningsih, 2016). Media is suitable to complement teaching methods because it is essential to convey information to students effectively (Puspitarini & Hanif, 2019;Suryadi et al, 2020;Y.…”
Section: Introductionmentioning
confidence: 99%